A Note on Cube-Full Numbers in Arithmetic Progression - Mingxuan Zhong; Yuankui Ma (Journal of Mathematics)
We obtain an asymptotic formula for the cube-full numbers in an arithmetic progression n≡lmod q, where q,l=1. By extending the construction derived from Dirichlet’s hyperbola method and relying on Kloosterman-type exponential sum method, we improve the very recent error term with x118/4029<q.